Consumption Behavior Analysis of Generation Z on Chinese Sports Brand Apparel with TAM-TPB Model (Journal of Fiber Bioengineering and Informatics, 2024)
Generation Z refers to those born between 1996 and 2010. Generation Z is entering the workforce andbecoming the leading consumer market force. Studying the consumption intentions of Generation Ztoward domestic sports brand apparel can significantly benefit the brand’s future business development.This study employs a questionnaire survey and incorporates factors from the Technology AcceptanceModel (TAM) based on the Theory of Planned Behavior (TPB) to investigate the factors influencingGeneration Z consumers’ online purchasing intentions for Chinese sports brand apparel. The resultsindicate that the behavioral intentions of Generation Z towards domestic sports brands are significantlypositively correlated with subjective norms, perceived behavioral norms, usefulness, and ease of use.